Tanacetipathes Opresko, 2001 (Cnidaria: Antipatharia: Myriopathidae) from Brazil, including two new species - Loiola, Livia L.; Castro, Clovis B. (Zootaxa, 2005)
The study of material obtained through dredging from off Brazil, in stations between Salvador (13° S) and the Cape of Sao Tome (22° S), and through scuba diving at the Abrolhos Reefs (18° S) revealed six species of Tanacetipathes Opresko, 2001. Two of these represent new species: T. longipinnula and T. thalassoros. Tanacetipathes barbadensis (Brook, 1889), T. hirta (Gray, 1857), and T. thamnea (Warner, 1981) represent first records from the South Atlantic. Tanacetipathes tanacetum (Pourtals, 1880) has been previously recorded off Brazil and it is probably the commonest species off Southeastern Brazil. Tanacetipathes paula Perez et al., 2005, is here considered a synonym of T. thamnea. An identification key to Tanacetipathes species is included along with illustrations of colonies, and a map of the genus distribution off Brazil, between 13° and 22° S.